Pengaruh Literasi Keuangan, Gaya Hidup Hedon Dan Financial Experience Terhadap Pengelolaan Keuangan Pada Mahasiswa Di Kabupaten Banyumas - Atingul Chusna; Slamet; Faizal Rizky Yuttama (MES Bogor, 2024)
Good and healthy money management is necessary in order to control one's financial condition. The financial literacy and financial management skills of Generation Z are still poor, especially students in Banyumas. Financial literacy is closely related to financial management, and the higher the level of financial literacy, the better the financial management skills. In addition to financial literacy, factors that can influence financial management behaviour are lifestyle and financial experience. The purpose of this study was to determine whether financial literacy, hedon lifestyle, and financial experience have a simultaneous influence on the financial management of students in Banyumas Regency. This research is a type of survey research with an explanatory approach. The sample size was 150 respondents with purposive sampling technique. This research instrument is a questionnaire. Data analysis in this study used multiple linear regression analysis. Based on the f test, it is obtained f count of 29,668 with f table of 3.06 and a significance value of 0.000. The significance value is smaller than α or 0.05 and f count 29.668 is greater than f table 3.06, the conclusion is that there is a significant simultaneous influence between financial literacy, hedon lifestyle, and financial experience on student financial management in Banyumas Regency.